Assessment of two antilipidemic drug subclasses (fibrates and statins) on embryogenesis in two model fish species (Danio rerio and Pimephales promelas) - Kingcade, Andrea, author; Ramsdell, Howard, advisor; Legare, Marie, committee member; Dooley, Greg, committee member; Garrity, Deborah, committee member; Winkelman, Dana, committee member (Colorado State University. Libraries, 2019)
The antilipidemic drug category is one of many pharmaceutical classes detected in effluent and surface water downstream of wastewater treatment plants. Nine antilipidemic drugs within two subclasses, fibrates (fenofibrate and gemfibrozil) and statins (atorvastatin, fluvastatin, lovastatin, pitavastatin, pravastatin, rosuvastatin, and simvastatin) are currently prescribed to humans. Embryogenesis in fish is a critical process in development that begins within hours of fertilization and progresses through important stages including gastrulation, neurulation, and organogenesis. To elucidate the effects antilipidemic drugs may have on these sensitive life stages, a mixture exposure study with all nine antilipidemic drugs was performed with zebrafish (Danio rerio, ZF) embryos, a developmental biology laboratory model fish species not native to the United States, at three nominal exposure levels: (a) 0.005 µM (Low), (b) 0.05 µM (Medium), and (c) 0.5 µM (High). An additional mixture exposure was performed on fathead minnow (Pimephales promelas, FHM) embryos, a toxicological model fish species found in most Colorado streams, at three nominal exposure levels: (a) 0.0005 µM (Ultra Low), (b) 0.005 µM (Low), and (c) 0.05 µM (Medium). Individual drug exposures to ZF embryos were also assessed at two nominal exposure levels: (a) drug-specific environmentally-relevant concentration (ERC Low) and (b) 1 µM (Very High). Test initiation began with blastulating embryos exposed to freshly-prepared exposure solution 4-6 hours post fertilization; ZF studies terminated at 72 hours and the FHM study terminated at six days post fertilization. Up to 15 observations were divided into four categories and evaluated: developmental toxicity, and muscle, yolk, and cardiovascular abnormalities. Complete mortality was observed in the ZF embryos exposed to 0.05 µM (Medium) and 0.5 µM (High) nominal concentrations in the mixture study and 51% of FHM embryos perished at the nominal 0.05 µM (Medium) exposure level. Developmental delays, delayed dechorionation, abnormal muscle fiber patterns, altered anterior-posterior (AP) axes, and the presence of hemorrhage and pericardial edema significantly increased in FHM embryos exposed to the nominal 0.05 µM (Medium) mixture treatment. Significant decreases in FHM heart rates were observed with the nominal 0.005 µM (Low) exposure compared to unexposed FHM embryos. Developmental delay evaluated as gastrulation defects was recorded in ZF embryos exposed to the nominal 0.5 µM (High) mixture concentration. Abnormal muscle fiber patterns, altered AP axes, abnormal intersegmental vessel development, and the presence of hemorrhage and edema (pericardial and yolk), were significantly increased compared to unexposed ZF embryos in the mixture study. Individual drug exposures did not elicit any toxicity to ZF embryos exposed to gemfibrozil, pravastatin, and rosuvastatin. Six of the nine individual drug exposures (fenofibrate, atorvastatin, fluvastatin, lovastatin, pitavastatin, and simvastatin) exhibited lethal and sublethal effects to ZF embryos. Embryos exposed to lovastatin or simvastatin, the only two prescribed in the prodrug lactone form, exhibited lethal effects in embryos exposed at the nominal 1 µM (Very High) treatment. Twelve sublethal effects were significant in one or more individual drug exposures at the nominal 1 µM exposure level. Abnormal yolk absorption by developing ZF embryos exposed to simvastatin at the nominal 2.4 x 10-5 µM (ERC Low) treatment was the only significant effect observed at an environmental concentration. Collectively, these observations illustrate that (a) embryos are sensitive to antilipidemic drug exposures during embryonic stages of development, (b) differences in species sensitivities occurred, and (c) differences between mixture and individual exposures of drugs were observed. These significant sublethal phenotypes would likely impact individual fish development and potentially the population as well if environmental concentrations increased. This model represents a potential tool for assessing sensitive, sublethal effects of pharmaceuticals in the environment.